New species and records of Trichoderma isolated as mycoparasites and endophytes from cultivated and wild coffee in Africa - María del Carmen H. Rodríguez (Nature Portfolio, 2021)
Abstract A survey for species of the genus Trichoderma occurring as endophytes of Coffea, and as mycoparasites of coffee rusts (Hemileia), was undertaken in Africa; concentrating on Cameroon and Ethiopia. Ninety-four isolates of Trichoderma were obtained during this study: 76 as endophytes of healthy leaves, stems and berries and, 18 directly from colonized rust pustules. A phylogenetic analysis of all isolates used a combination of three genes: translation elongation factor-1α (tef1), rpb2 and cal for selected isolates. GCPSR criteria were used for the recognition of species; supported by morphological and cultural characters. The results reveal a previously unrecorded diversity of Trichoderma species endophytic in both wild and cultivated Coffea, and mycoparasitic on Hemileia rusts. Sixteen species were delimited, including four novel taxa which are described herein: T. botryosum, T. caeruloviride, T. lentissimum and T. pseudopyramidale. Two of these new species, T. botryosum and T. pseudopyramidale, constituted over 60% of the total isolations, predominantly from wild C. arabica in Ethiopian cloud forest. In sharp contrast, not a single isolate of Trichoderma was obtained using the same isolation protocol during a survey of coffee in four Brazilian states, suggesting the existence of a ‘Trichoderma void’ in the endophyte mycobiota of coffee outside of Africa. The potential use of these African Trichoderma isolates in classical biological control, either as endophytic bodyguards—to protect coffee plants from Hemileia vastatrix, the fungus causing coffee leaf rust (CLR)—or to reduce its impact through mycoparasitism, is discussed, with reference to the on-going CLR crisis in Central America.